The unusual presentation of ceacal cancer with synchronous tumor at descending colon: a case report - Mohamad, Ikhwan Sani; Che Alhadi, Shahidah; Zakaria, Zaidi; syed abd aziz, syed hassan (Sciene and Education Publishing (SciEP), 2014)
Synchronous primary colorectal cancer is rare and only occurs in 2% to 11% of all colorectal cancers. Thus, preoperative or intraoperative detection of synchronous tumor is vital because if they are not recognized, they may present at an advanced stage, thereby reduce the probability of cure. Early identification of synchronous tumor may alter the extensiveness of the surgical procedure in order to decide for strategic therapeutic management.